Towards a Sustainable Local Development of Instructional Material: An Impact Assessment of Locally Produced Videos on EFL Learners’ Skills and Individual Difference Factors - Lasekan, Olusiji; Godoy, Margot (Frontiers in Psychology, 2020)
The purpose of this paper is to conceptualize the sustainability of local videos development, their integration in the EFL classroom, and their impact on students’ learning outcomes. The research aims as well to assess the impact of the videos on learners’ English language skills achievement and individual difference factors. We recruited a random sample of 100 and 76 students learning different levels of English in our English institute through an online survey. A cross-sectional study of perceived English language skill achievement and individual difference factors such as motivation, attitude, and cultural awareness was carried out. A combination of quantitative and qualitative approaches was used for data collection and analysis. Our conceptual framework showed that the sustainability of the local video production and its integration in the EFL classroom depends on the university’s funding policy, which is subjected to the positive impact of the videos on students’ learning outcomes. Also, the obtained results revealed that the videos fostered learners’ English language skills as well as their motivation to learn the language, positive attitudes toward its integration, and local cultural awareness. This work contributes to existing knowledge of sustainable local curriculum development by providing the first empirical evidence on the positive impact of sustainable local videos as an instructional material on students’ learning outcomes.